Implikasi Hukum terhadap Notaris yang Menjalankan Kewenangan pada Masa Cuti - Listya Sari Pertiwi; Tetti Samosir (Jurnal Hukum Lex Generalis, 2025)
A notary is very likely to be exposed to legal entanglements, not only internal factors that come from oneself, such as carelessness, non-compliance with procedures, or violations of Professional Ethics, an example is when the notary exercises his authority during the leave period. This study is a normative study that studies the purpose of law, the values of justice, the validity of the rule of law, legal concepts, and legal norms. Normative legal research can also be regarded as a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues faced. It can also be said that legal research is carried out to produce arguments, theories, or concepts as prescriptions or answers to the problems faced. In this provision, the Notary who is on leave is obliged to appoint a replacement notary to carry out his authority and responsibility, so that the notary concerned is no longer authorized to carry out the duties of his position until the leave period ends. If the notary continues to exercise this authority, the resulting deed is not within the provisions, the Notary who is on leave is obliged to appoint a replacement notary to exercise his authority and responsibility, so that the notary concerned is no longer authorized to carry out his duties until the leave period ends. If the notary continues to exercise this authority, the resulting deed does not meet the formal requirements of the authentic deed as stipulated in the UUJN, and therefore loses its authenticity value. The deed can only be considered as a deed under hand that does not have perfect force of proof. This situation not only violates the normative provisions, but also damages the joints of professional ethics which requires the integrity and obedience of notaries to the law and code of ethics.